Conventional versus accelerated beef production with carcass electrical stimulation - Dikeman, Michael E.; Dayton, A.D.; Hunt, Melvin C.; Kastner, Curtis L.; Axe, J.B.; Ilg, H.J. (American Society of Animal Science, 2008)
Sixty-four 8-too-old steers, produced from 7/8 Simrnental sires mated to crossbred dams, averaged 265 kg initial weight. Forty-eight steers were assigned to an Accelerated (ACC) production system, while 16 steers were assigned to a Conventional (CONV) production system. Steers on the ACC system were fed an 85% concentrate diet; steers on the CONV system were backgrounded for 110 d on a high silage diet and then finished on an 85% concentrate diet. The ACC steers were slaughtered in three groups at average weights of 438, 492 and 554 kg; CONV steers were slaughtered at 591 kg. Days-on-feed were 139 (ACC-I), 174 (ACC-II), 2,0,.2 (ACC-III) and 284 (CONV), respectively. At slaughter, one side of the carcass was pulse-electrically stimulated (ES) with 400 V at 45 min postmortem and the other side served as a nonelectrically stimulated control (C). Semimembranosus (SM) and longissimus (LD) C and ES steaks were removed at 48 and 24 h postmortem, respectively, vacuum packaged, aged 6 d at 2 C, frozen and later thawed for trained sensory panel and Warner-Bratzler shear (WBS) evaluations. Overall average daily gains were not different among slaughter groups, but CONV steers gained faster (P<.05) during the finishing phase than ACC steers. Metabolizable energy:gain ratios were not different among treatments, but dry matter:gain ratios were higher (P<.05) for CONV steers than for ACC-I and ACC-II steers. The CONV steers had lower (P<.05) dressing percentages than ACC-II and ACC-III steers. Lipid of the 9-10-11th rib section was higher (P<.05) and protein and water were lower (P<.05) for ACC-III than for ACC-I and ACC-II steers, but not different (P>.O5) from CONV steers. Electrical stimulation decreased (P<.05) 2-, 4- and 6-h pH readings. The LD steaks from ACC-II and ACC-III steers were at least equal in all sensory traits, except juiciness, to those from CONV steers. The SM steaks from CONV steers had the highest WBS force and lowest sensory scores. Electrical stimulation decreased (P<.0$) LD myofibrillar and overall tenderness scores, but had no effect on SM palatability.
Keywords: Food science; Bovidae; Perfomance; Carcasses; Nutrition; Palatability; Electrical treatment